(untitled) (Editora Impacto Científico, 2025)
The beauty industry is one of the fastest-growing in the personal hygiene, perfumery, and cosmetics sectors. Brazil is known for its biodiversity, with its oils widely used in the cosmetics and pharmaceutical industries. The overall objective of this study was to develop a cosmetic moisturizing cream formulation containing Brazil nut oil (Bertholletia excelsea H. B. K.) and analyze its physicochemical and organoleptic characteristics, following ANVISA (Brazilian Health Regulatory Agency) standards. The oil yield was 13.5%, lower than in other studies. The organoleptic characteristics of the oil were acceptable, with a refractive index of 1.470 and a density of 0.879 g/cm³, values in line with expectations. The oil’s pH was lower than expected, registering 04.48. After the analyses, the moisturizing cream containing Brazil nut oil was produced and evaluated twice: on the first day and after 90 days. Organoleptic analysis revealed no changes in color or odor, but its appearance became denser. The refractive index was 1.654 and 1.693 at 20°C, with a density of 0.962 g/cm³ and 0.914 g/cm³, respectively. The pH of the cream was 5.11, while after 90 days, it changed to 5.28, a value within the standard for skin. The cream was considered stable and of good quality. DOI: https://doi.org/10.56238/edimpacto2025.090-023